Pengaruh Indikator Kinerja Keuangan Terhadap Return on Asset PT BRI Agroniaga Tbk - Mubarok, Husni (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2022)
This study aims to analyze the Effect of Financial Ratio Indicators on Return on Assets at PT BRI Agroniaga Tbk 2007-2020. The research creates a quantitative case study descriptive model that produces a partial test of the CAR variable of 0.754 showing the most strong influence of the hypothesis Ho is accepted by normal distributed residuals on ROA while the simultaneous test is carried out together with the independent variable indicator 0.850 the level of correlation is very strong, the dependent variable hypothesis Ho is accepted the residual is normally distributed against ROA.